Álgebras de Lie, grupos de Lie e aplicações a teoria de ações de semigrupos - Michel Teston Semensato (2010)
The objective of this work is to present a study of algebras of Lie and the groups of Lie, as well as the linking between the two concepts, with the objective to apply this theory in the theory of action of semigroups. Initially, we will study the groups of Lie and the relations of this concept with algebras of Lie. Finally, we will present a revision of the main results on control sets for action of subsemigroups of semisimple Lie groups, in its flag manifolds. In accordance with the type of simple system of roots, we will find upper bounds for the number of effective control sets on the flag manifolds of the real simple non-compact Lie groups